Risk factors of musculoskeletal disorders (MSD) among palm oil mill workers - D. M. Y., Nur Athirah; Karuppiah, Karmegam; Mohd Tamrin, Shamsul Bahri; R., Shahmi; S., Sivasankar; A. S., Putri (Perpustakaan Sultan Abdul Samad, Universiti Putra Malaysia, 2015)
The palm oil industry is the fourth largest contributor to the Malaysian Gross National Income (GNI) but the importance of this industry to the nation’s economy does not preclude them from the risk of being affected by the occurrence of musculoskeletal disorders (MSD) among the workers in palm oil mills. Previous studies carried out have not properly explained the exact reasons for the occurrence of musculoskeletal disorders (MSD) among the palm oil mill workers. Thus, this study aim to determine the association between risk factors and MSD among palm oil mill workers. A total of 120 male workers were consecutively enrolled in this crosssectional study. Information on sociodemographic, working, lifestyle, health and injury factors were collected via questionnaire and face-to-face interviews. A high lifetime prevalence of MSD (71.7 percent) among palm oil mill workers was found. However, the one-year prevalence of MSD among the same population was only 50.8 percent. Logistic regression analysis adjusted for age, Body Mass Index (BMI) and smoking revealed that the risk factors: history of previous injury [2.35, 95 percent CI 1.12-4.93], Osteoarthritis [3.9, 95 percent CI 1.568-9.708] and perception of exertion [8.09, 95 percent CI 1.358-48.170] was found to be significantly associated with MSD symptoms reported in the past 12 months. As a conclusion, exposure to the combination of these risk factors may lead to an increased risk of developing MSD among palm oil mill workers.